2015
DOI: 10.1111/tri.12721
|View full text |Cite
|
Sign up to set email alerts
|

Underweight and obesity increase the risk of mortality after lung transplantation: a systematic review and meta-analysis

Abstract: SummaryMany studies have found an association between abnormal body mass index (BMI) and poor outcomes among lung transplant recipients. We performed a systematic review and meta-analysis to identify outcomes associated with an abnormal pretransplant BMI after lung transplantation (LTx). The MEDLINE and EMBASE databases were searched from inception to May 2015 with focus on original observational studies with post-transplant survival data in candidates with abnormal BMI (underweight, overweight, or obese). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 39 publications
4
44
1
Order By: Relevance
“…This finding is consistent with other studies supporting an association between obesity and risk of PGD [21, 22]. In addition to PGD, obesity also affects other short and long term outcomes after lung transplantation[23, 24]. Weight management is a challenge for many potential lung transplant recipients.…”
Section: Modifiable Clinical Risk Factorssupporting
confidence: 90%
“…This finding is consistent with other studies supporting an association between obesity and risk of PGD [21, 22]. In addition to PGD, obesity also affects other short and long term outcomes after lung transplantation[23, 24]. Weight management is a challenge for many potential lung transplant recipients.…”
Section: Modifiable Clinical Risk Factorssupporting
confidence: 90%
“…Several studies have found an association between recipient increased body mass index and increased risk of PGD. Most of them have been analyzed in two successive systematic reviews and meta‐analyses ; others have been described more recently . Moreover, Shah et al .…”
Section: Discussionmentioning
confidence: 99%
“… developed prediction models for PGD and showed that patients with a normal BMI have a lower risk of PGD and Upala et al . reported an increased risk of mortality after lung transplantation in recipients with underweight or obesity. By contrast, to the best of our knowledge, there is no study on the relation between body mass index and NO administration in the field of lung transplantation and we can only speculate that the increased risk of iNO dependency associated with the increase in body mass index could be due to the relation between permanent inflammatory state, due to obesity and leptin‐mediated lung inflammation and the production of pro‐inflammatory cytokines from adipose tissues and macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…Relative to having healthy body weight, being obese or underweight is associated with a higher risk of death among female breast cancer patients [7] . Lung transplant candidates who are underweight or obese have a higher risk of post-transplant mortality than recipients with a healthy weight [8] .…”
Section: Is Being Underweight As Bad For Your Health As Being Obese? mentioning
confidence: 99%
“…Researchers have applied this framework in studies of various health-related phenomena such as effects of prenatal care on birth weights [14] ; household production and demand for health inputs and their effects on birth weights [15] effects of childhood and education on health [16] ; the impact of maternal smoking on child neurodevelopment [8] and the relationship between household production, fertility and child mortality [17] . Within the health production framework, body weight classes are inputs in the production of general, physical, and mental health.…”
Section: Study Modelmentioning
confidence: 99%